Productive Organizations: The Human-Computer Interaction in Black Mirror - de Souza Assumpção, Georgia (2023)
The series Black Mirror, broadcast between 2011 and 2023 on Netflix, has become a media phenomenon and its episodes have shown ways of human-computer interaction. The series’ name refers to the fact that when a screen is turned off, it becomes a black mirror that reflects the user’s image. This paper[1]  aims to analyze the side effects of human-computer interaction in Black Mirror’s production organizations. This research used discourse analysis, mainly from Mikhail Bakhtin’s contributions. The method consisted of three stages that relied on the collaboration of Industrial Engineering students. The research included undergraduate and postgraduate students working collectively, since this procedure integrates teaching and research and helps beginners develop a critical sense. The results indicate that in Black Mirror organizations there is a transition from the concept of human factors to cyborg factors, as well as the use of human-computer interaction to promote social control.   [1] This study was partly financed by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001. The first author thanks the Brazilian Institute of Geography and Statistics (IBGE) for allowing her to take a temporary leave of absence to carry out the Sandwich Doctoral Program abroad (PDSE).